Efficiency Optimization of the Main Operating Points of an EV Traction Motor - Gi-haeng Lee; Yong-min You (Applied Sciences)
Motor efficiency presents a trade-off between low-speed and high-speed regions. Additionally, the cross-sectional area of hairpin motors employing rectangular wires is larger than that of round wires, thereby amplifying AC copper losses. As the operating speed increases, the AC copper loss also becomes more pronounced; therefore, efficiently determining the optimal design point considering these characteristics is essential. This study optimizes the efficiency of an electric vehicle (EV) simulation is conducted using MATLAB 2024, and the main operating points according to the driving cycle are selected. For the EV simulation to select the main operating points, the driving cycle of the multi-cycle test method, which is used for measuring domestic driving range, is considered to enhance the validity of the operating points. The efficiency optimization of the main operating points was performed considering the AC copper loss, and essential parameters such as the torque ripple and total harmonic distortion of the back-electromotive force were incorporated as constraints. Furthermore, the predictive performances of the 11 metamodels were compared to identify the most suitable metamodel for the output and design variables. Subsequently, the selected metamodel was integrated with four optimization algorithms to optimize the design.